Waterlogging and its Possible Reclamation Studied in a Coastal Block of Odisha using Remote Sensing and GIS - RAUT, SHISHIR; KAR , G.; SAHOO, N. (Journal of the Indian Society of Coastal Agricultural Research, 2023)
.